Risk factors for gastric cancer in patients with Lynch syndrome. Issue 9 (14th July 2022) - Ortigão, Raquel; Brito, Mariana; Pinto, Cláudia; Sá, Inês; Libânio, Diogo; Dinis-Ribeiro, Mário; Brandão, Catarina
Abstract : Introduction: The cumulative lifetime risk of gastric cancer (GC) in patients with Lynch syndrome (LS) is reported to be 8%. There is limited evidence on specific risk factors for GC and no agreement among guidelines on gastric endoscopic surveillance schedule in LS patients. Aims and methods: We conducted a retrospective cohort study to identify risk factors for gastric precancerous conditions (chronic atrophic gastritis and intestinal metaplasia) and GC in patients with LS and a case–control study to compare the prevalence of these conditions with a control group. Results: We included 385 LS patients (40.5% male, mean age 49.0 years). During a median follow-up period of 48 months (interquartile range, 24–84 months), precancerous conditions were identified in 110 patients (34%) and the prevalence of advanced stages of atrophic gastritis was 3% for OLGA III/IV and 0.6% OLGIM III/IV. Family history of GC was significantly associated with OLGA III/IV ( P = 0.020). Among LS patients, 10 patients (2.6%) were diagnosed with GC (incidence rate of 5/1000 persons-year). Older age and OLGA III/IV were identified as risk factors for GC ( P < 0.001). When compared with controls, patients with LS had significantly higher rates of Hp infection ( P = 0.035) and lower OLGA and OLGIM stages ( P < 0.001 and P = 0.026, respectively). Conclusion: In our cohort, the incidence of GC and advanced stages of atrophic gastritis was low. Older age and OLGA III/IV were associated with a higher risk of GC. Identification of risk factors for GC in LS patients can help tailoring endoscopic surveillance.